Church history : From Christ to the Pre-Reformatión. The Rise and Growth of the Church in Its Cultural, Intellectual, and Political Context. - Fergunson, Everett (Zondervan Academic, 2013)
Church History offers a unique contextual view of how the Christian church spread and developed. It did so not in a vacuum, but in a setting of times, cultures, and events that both influenced and were influenced by the church. Church History looks closely at the integral link between the history of the world and that of the church. Volume one explores the development of the church from the days of Jesus to the years prior to the Reformation. Filled with maps, charts, and illustrations, it offers overviews of the Roman, Greek, and Jewish worlds; insights into the church’s relationship to the Roman empire, with glimpses into pagan attitudes toward Christians; the place of art and architecture, literature and philosophy, both sacred and secular; and much more, spanning the time from the first through the thirteenth centuries. Volume One Content Overview 1. The Setting for the Story’s Beginning 2. Jesus and the Beginnings of the Church 3. The Subapostolic Age 4. The Church and the Empire 5. Heresies and Schisms of the Second Century 6. The Defense Against Rival Interpretations 7. The Fathers of the Old Catholic Church and Their Problems 8. Church Life in the Second and Third Centuries 9. Development of the Church During the Third Century 10. Diocletian and Constantine: On the Threshold of the Fourth Century 11. The Church in the Fourth Century: Doctrine, Organization, and Literature 12. The Church in the Fourth and Early Fifth Centuries: Monasticism, Expansion, Life, and Worship 13. Christological Controversies to Chalcedon 14. Augustine, Pelagius, and Semipelagianism 15. Transitions to the Middle Ages: Germanic Migrations, Doctrinal Developments, and the Papacy 16. Eastern and Western Churches in the Fifth and Sixth Centuries 17. The Eastern Church from the Seventh to Eleventh Centuries 18. The Western Church from the Seventh to Ninth Centuries 19. Decline and Renewal of Vitality in the West: The Ninth to Eleventh Centuries 20. The Papal Reform Movement and the First Crusade 21. Intellectual Revival: The Rise of Scholasticism 22. Monastic, Literary, Political, and Cultural Activities in the Twelfth Centuries 23. The Glory of the Western Medieval Church: The Thirteenth Century 24. Portents of Decline